Effects of Nevirapine and Efavirenz on HDL Cholesterol Levels and Reverse Cholesterol Transport in Mice - Tohyama, Junichiro (2008)
OBJECTIVE: The mechanism by which non-nucleoside reverse transcriptase inhibitors (NNRTIs) increase HDL cholesterol (HDL-C) in HIV+ patients and the benefits of this with respect to cardiovascular risk are not known. Studies were conducted to test the hypothesis that NNRTIs have a beneficial effect on HDL-C and reverse cholesterol transport (RCT). METHODS: LDLr −/− and hA-I transgenic mice were fed a Western diet containing either nevirapine (20 mg/kg/day), efavirenz (10 mg/kg/day), or diet alone. hA-I transgenic mice underwent a study to measure RCT (measured by excretion of macrophage [(3)H]-cholesterol into HDL and feces) at 8 weeks. RESULTS: LDLr −/− and hA-I transgenic mice treated with nevirapine and efavirenz had a significant increase in HDL-C level (up to 23% in hA-I transgenic) at 4 weeks. However, there was no difference in HDL levels beyond 4 weeks of treatment. At 4 weeks, the FPLC profile of hA-I transgenic mice showed an increase in large HDL. hApoA-I transgenic mice treated with efavirenz for 4 weeks had increased expression of human apoA-I in liver and an increased human apoA-I production rate. Incubation of plasma from hA-I transgenic mice treated for 4 weeks with [(3)H]-cholesterol-labeled macrophages revealed increased cholesterol efflux to plasma from mice treated with efavirenz and nevirapine. Following injection of hA-I transgenic mice treated for 8 weeks with [(3)H]-cholesterol-labeled macrophages, RCT was increased in the efavirenz (p=.01) group and trended towards an increase in the nevirapine (p=.15) group. CONCLUSION: Nevirapine and efavirenz transiently increased HDL-C in LDLr −/− and hA-I transgenic mice fed a Western diet that was associated with increased apoA-I production. An increase in RCT in hA-I transgenic mice at 8 weeks despite no difference in HDL levels indicates that these drugs affect additional factors in the RCT pathway that enhance cholesterol efflux from the macrophage and peripheral tissues to plasma and delivery to liver for excretion. These results suggest that treatment with NNRTIs has a beneficial effect on cholesterol efflux and RCT.